Sintesis Nanokitosan Menggunakan Metode Gelasi Ionik Dengan Variasi Konsentrasi Asam Formiat - Allailus Syah Safara; Ahmad Fadli; Sunarno Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Particles at the nanometer scale have unique physical properties compared to particles at larger sizes, especially in improving the delivery quality of drug compounds. The study aims to synthesis nanochitosan using the ionic gelation method and determined the effect of variation in the concentration of formic acid on the characteristics of nanochitosan. The procedure for making nanochitosan is chitosan dissolved in formic acid (0.2% and 2%) by stirring using a magnetic stirrer. After that, the STPP solution (0.1%) at the chitosan:STPP 5:1 volume ratio was added to the chitosan solution. Stirring was carried out for 1 hour with a stirring speed of 1200 rpm. Furthermore, the nanochitosan was characterized by using Particle Size Analyzer (PSA). Results of the research found that the polydispersity index of chitosan-STPP particles was decreased when the concentration of formic acid was increased, at the concentration of STPP (0.1%) and concentrations of formic acid (0.2% and 2%) are 0.438 and 0.178 respectively. Keywords: formic acid, ionic gelation, nanochitosan, sodium tripolyphosphate